Penelusuran Metode Pekerja Sosial dengan Cara Observasi di Panti Asuhan Medan - Pasaribu, Zico Ananda; Widya Yossi Hutapea; Berlian Seladamai Yanti S; Maria Magdalena Br Surbakti; Riska Akila Zahra (Yayasan Literasi Sains Indonesia, 2023)
In this journal we will discuss the methods used by the social workers of the Cahaya Hati Anugerah Panti Foundation in providing services to orphanage children. The existence of the Orphanage Manager or social worker is sure to have a big effect on the growth of the orphans. The right method will be a good solution to the problems they experience. Orphanage children need a social worker as a substitute for the role of parents who should be a place to share affection and complaints about problems and suggestions for solving these problems. The process of solving problems on their own takes quite a long time considering the age of the children at the orphanage. The purpose of this writing is as a result of project base learning activities. The method used is observation and interviews in the data collection process. Existing literature sources are also used to assist discussion analysis. The problems that occur in this orphanage also vary, such as the lack of finance for the needs of the orphanage, the house that has not been renovated for the comfort of the caretaker and the orphans and many other problems. We do this activity as a form to help find solutions to how to solve problems that occur in orphanages.